Oral health status and treatment needs among obstructive sleep apnea patients in Jodhpur, Rajasthan - Neha Shaktawat; Minha Manzoor; Nazish Khan; Ajaz A Dar; Rajendra S Bhati; Arpan Biswas (Wolters Kluwer Medknow Publications, 2023)
Background: Obstructive sleep apnea (OSA) is a sleep disorder characterized by periodic and repetitive partial or complete collapse of the upper airway during sleep, resulting in reduced ventilation (hypopnea) or absent ventilation (apnea).Materials and Methods: The present study was conducted on 100 adult OSA patients attending hospitals of Jodhpur and the dental clinic in Vyas Dental College and Hospital in Jodhpur city. The sample consisted of 65.0% males and 35.0% females, belonging to 18 years ≥60 years of age with a mean age of 47.61 ± 8.53.Results: In our study, we have used AHI for the assessment of OSA, the major significant association (P = 0.001) was seen between AHI and periodontitis. The finding suggest that the prevalence of periodontitis is greater among patient with OSA with almost 39 patients with AHI value between 11to15 having loss of attachment between 4 mm ≥8 mm. Conclusion: Obstructive sleep apnea is acting as a significant risk factor for major Dental diseases. The study concludes that there was a significant association found between oral health status and OSA patients.